Quality Analysis Of Logistics Management Information System Software Using MCALL: Quality Analysis Of Logistics Management Information System Software Using MCALL - Aziz Ma'sum; Jejen Samsul Aripin (Institute of Computer Science (IOCS), 2020)
The development of information technology is so rapid to make the needs of technology increase. The progress of an organization depends on the information technology used. But in using an information technology must be concerned with the quality of information technology used. Software testing is one of the most important things in determining software quality. This research was conducted to determine the quality of the Logistics Management Information System software that has been used at the Bandung Institute of Technology. This test uses the McCall model framework in which the quality factor variables tested are correctness, reliability, efficiency, integrity, usability, maintainability, flexibility, testability, portability, reusability and interoperability. The data collection method used is the observation method used for information gathering by directly observing the activities of the research object environment and the interview method used to collect data regarding information on Logistics Management Information System software through interviews with several employees who understand the Information System system. Logistics Management. Based on the results of research that has been done there are still some shortcomings including the factors of reliability, efficiency, usability and interopability. While the factors of correctness, maintainability, flexibility, testability, portability and reusability have met the software quality factors and organizational needs.